The Story of Us: Older and Younger Couples' Language Use and Emotional Responses to Jointly Told Relationship Narratives. (23rd June 2022) - Wilson, Stephanie J; Kiecolt-Glaser, Janice K
Abstract: Objectives: Social-emotional well-being is said to improve over adulthood, and studies of couples' age differences have focused primarily on marital conflict. The way couples discuss their relationship story predicts marital quality among newlyweds and long-married couples alike, yet older and younger couples' accounts have never been compared. The current study examined age differences in couples' use of I/we-talk, emotion words, and immediacy (i.e., an urgent and unresolved style) during a relationship history discussion and their subsequent mood reactivity and appraisals. Method: Married couples ( N = 186 individuals within 93 couples, aged 22–77) recounted the story of their relationship then rated the discussion and their negative mood. Mediation models assessed the 3 linguistic features as parallel dyadic mediators linking couple age to negative mood responses and appraisals, controlling for global marital satisfaction, and baseline negative mood. Secondary analyses examined partners' concordance in language use. Results: Compared with younger couples, older couples used more positive than negative words and less immediacy which, in turn, was associated with husbands' and wives' less negative mood and more positive appraisals, only among husbands. Partners in older couples used more similar I/we-talk and emotional language, but these were unrelated to mood or appraisals. Discussion: This study extends our understanding of how marital interactions differ by age in the understudied context of relationship history discussions, which may grow increasingly important for couples' well-being with older age. Findings broadly align with social-emotional aging theories and uncover novel linguistic features relevant to the age-related emotional benefits of joint reminiscing.